HIV-1 Infection Accelerates Age According to the Epigenetic Clock - Horvath, Steve (J Infect Dis, 2015)
Background. Infection with human immunodeficiency virus type 1 (HIV) is associated with clinical symptoms of accelerated aging, as evidenced by the increased incidence and diversity of age-related illnesses at relatively young ages and supporting findings of organ and cellular pathologic analyses. But it has been difficult to detect an accelerated aging effect at a molecular level. Methods. Here, we used an epigenetic biomarker of aging based on host DNA methylation levels to study accelerated aging effects due to HIV infection. DNA from brain and blood tissue was assayed via the Illumina Infinium Methylation 450 K platform. Results. Using 6 novel DNA methylation data sets, we show that HIV infection leads to an increase in epigenetic age both in brain tissue (7.4 years) and blood (5.2 years). While the observed accelerated aging effects in blood may reflect changes in blood cell composition (notably exhausted cytotoxic T cells), it is less clear what explains the observed accelerated aging effects in brain tissue. Conclusions. Overall, our results demonstrate that the epigenetic clock is a useful biomarker for detecting accelerated aging effects due to HIV infection. This tool can be used to accurately determine the extent of age acceleration in individual tissues and cells.